2014
DOI: 10.3109/13880209.2014.914230
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of propolis against cyclophosphamide-induced toxicity in mice

Abstract: In conclusion, propolis might be considered an effective agent in ameliorating the toxicity resulted from CTX treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 37 publications
8
29
0
Order By: Relevance
“…Kidney histological examination contributes to diagnostic accuracy in druginduced kidney damage and remains a valuable tool in assessing drug-induced kidney damage (48). CP renal pathology is often characterized by necrotic changes in kidney structure (49). This study observed kidney pathologic changes characterized by tubular necrosis, and infiltrations by inflammatory cells in CP-treated rats.…”
Section: Discussionmentioning
confidence: 69%
“…Kidney histological examination contributes to diagnostic accuracy in druginduced kidney damage and remains a valuable tool in assessing drug-induced kidney damage (48). CP renal pathology is often characterized by necrotic changes in kidney structure (49). This study observed kidney pathologic changes characterized by tubular necrosis, and infiltrations by inflammatory cells in CP-treated rats.…”
Section: Discussionmentioning
confidence: 69%
“…Propolis has a long history of being used in traditional medicine (Gavanji & Larki, 2015). Ghisalberti et al (1978) reported that propolis extracts have a broad spectrum of biological activities, namely antioxidant (Nagai et al, 2003;Zhang et al, 2016), antibacterial (Choi et al, 2006), antiviral (Marcucci, 1995;Yildirim et al, 2016) and anticancer (Kumazawa et al, 2004;El-Naggar et al, 2015) due to its related therapeutic compounds including polyphenols and flavonoids. Various molecules have been identified from propolis collected from different parts of the world, including phenolic acids, flavones, flavonols and flavanones.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy with cyclophosphamide is known to affect the performance of the immune system, in terms of reduction in the number of WBCs, resulting in increased susceptibility to viral and bacterial infections (El‐Naggar, Alm‐Eldeen, Germoush, El‐Boray, & Elgebaly, ). To determine the success of this model and whether the mixture of polysaccharides and polyphenols enhances immunity, we evaluated the population of peripheral blood WBCs in mice.…”
Section: Resultsmentioning
confidence: 99%